Effect of Antenatal Care and Postnatal Care on Exclusive Breastfeeding Practice: Meta Analysis - Agusningtyas, Nisia Hari; Dewi, Yulia Lanti Retno; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: The World Health Organization (WHO) reports that 2 out of 3 babies do not get exclusive breastfeeding and only 41% of babies aged 0-6 months get exclusive breastfeeding. It is believed that ANC and PNC examinations can increase the possibility of mothers to start and maintain exclusive breastfeeding, because mothers will receive information and support about the benefits of exclusive breastfeeding, the importance of giving colostrum, and the right technique for positioning and attachment in breastfeeding. This study aims to analyze the effect of ANC and PNC on the practice of exclusive breastfeeding. Subjects and Method: This study is a systematic and meta-analysis study, with the following PICO Population = Breastfeeding mothers. Intervention = ANC <4 times and no PNC. Comparison = ANC ≥4 times and PNC. Outcome = Exclusive breastfeeding. The articles used in this study were obtained from several databases including PubMed, Google Scholar, EBSCO, Springer Link, Science Direct, and Pro Quest. The keywords used are “ANC and exclusive breastfeeding”, “PNC and exclusive breastfeeding”. The inclusion criteria were full-text article observational study designs. Articles are collected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application. Results: Based on the results of a meta-analysis of 9 primary studies originating from Ethiopia, Tanzania, The Gambia, Saudi Arabia, and Indonesia, it was found that regular ANC, which was 4 times or more, has the possibility of giving exclusive breastfeeding by 1.55 times ANC (aOR=1.55; 95% CI=1.29 to 1.88; p=0.001) and mothers who conduct PNC have the possibility of giving exclusive breastfeeding by 2.43 times (aOR=2.43; 9 5%CI=1.78 to 3.31; p=0.001). Conclusion: ANC and PNC examinations can improve the practice of exclusive breastfeeding. Keywords: ANC, PNC, and Exclusive Breastfeeding Correspondence: Nisia Hari Agusningtyas. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: harinisia@gmail.com. Mobile: +6282138344620